PENGARUH PENERAPAN GOOD GOVERNMENT GOVERNANCE DAN KOMPETENSI SUMBER DAYA MANUSIA TERHADAP KUALITAS INFORMASI LAPORAN KEUANGAN - Zai, Ferra Pratiwi; Purba, Sahala; Nainggolan, Arison (JURNAL MUTIARA AKUNTANSI, 2020)
This study aims to examine the effect of the implementation of Good Government Governance (GGG) and Human Resources Competence on the quality of financial statement information in BPKPAD, West Nias Regency. This research is a quantitative study using primary data and using census in collecting data. To collect the data, researchers used a questionnaire given to all BPKPAD staff in West Nias Regency. The total number of staff BPKPAD Kab. West Nias as many as 50 people. To analyze the data, researchers used descriptive statistical analysis methods, classic assumption tests and multiple linear regression analysis. Of the 50 questionnaires distributed, only 47 questionnaires could be processed. Partially, the results of the study show that GGG has a significant influence on the quality of financial statement information and the competence of human resources has a significant influence on the quality of financial statement information. Together GGG and human resource competencies significantly influence the quality of financial statement information on BPKPAD in West Nias Regency.